Economical use of water in cotton knit dyeing industries of Bangladesh. (15th March 2022) - Chakraborty, Rathin; Ahmad, Farid
Abstract: Textile knit dyeing industries of Bangladesh are playing a significant role in the country's economy and retain above forty percent of the total annual export performance. Economical use of water in the knit dyeing industries may lead to reduce water consumption significantly, thereby availing environmental sustainability. This study was undertaken to explore the possibility of minimizing water use in the cotton knit dyeing process without hampering the fabric quality and find out the resulting environmental and economic benefits. Currently, there are no published color-wise water consumption data for dyeing one kg of knit fabric available from Bangladesh cotton knit dyeing industries. Therefore, the primary information about water consumption has been generated by site visiting and auditing bulk production of some selected cotton knit dyeing industries. Material balance and right first time (RFT) approaches are exploited for generating stepwise water consumption scenarios. Minimum volume of adequate water required for each reactive dyeing has been estimated. The total volume of water consumed by cotton knit dyeing industries of Bangladesh was about 85.87 million cubic meters in the year 2019–2020. It has been estimated that 1 L less water consumption to produce 1 kg of fabric can save 7.80 percent of chemical cost. These estimates suggest that it is imperative to monitor every dyeing step carefully for reducing water consumption without compromising the quality of dyeing and fabric. The analyses of the collected knit dyeing processing data reveal that water consumption quantity varies with the factors like design of the dyeing machine, efficiency of the machine pump, types of wet processing and fabric, know-how (knowledge) and with adaptation of new technologies or processes. Many new approaches can be brought into practice to minimize water use during cotton knit dyeing processes. Finally, some sustainable alternative technologies, prospective techniques and recommendations are set forth based on the authors' extensive inspection, experience, spill-off knowledge and received information from previous studies to prompt economical use of water, thereby reducing water consumption in cotton knit dyeing industries of Bangladesh. The study concludes that predictive approaches, along with preventive measures for the reduction of water consumption in dyeing processes using sustainable technologies and practices, will make a paradigm shift from the reactive approach for wastewater management to the preservation of natural resources. Highlights: Benefits of economical use of water in cotton knit dyeing industries are discussed. Material balance approach is used for generating stepwise water consumption scenarios. Minimum volumes of adequate water for Reactive dyeings are estimated. 1 L less water consumption per kg fabric can reduce 12.80% chemical consumption. Options for reducing water consumption in Bangladesh textile industries are proposed.